KAJIAN PENGGUNAAN WETFIX BE PADA BETON ASPAL CAMPURAN PANAS BERGRADASI SUPERPAVE - Rikki Sofyan Rizal; Anni Susilowati; Heri Susanto (Jurnal Ilmiah Teknologi Infomasi Terapan, 2019)
This research aims to evaluate the uses of Wetfix BE in graded superpave asphalt concrete hot mix for wearing course layers of flexible pavement, from the aspect of quality, which is characteristic of Marshall, deformation, surface roughness, and costs. In this research the use of Wetfix BE variations were 0.0%, 0.2%, 0.3%, and 0.4% of the KAO 6%. From the research, the use of Wetfix BE in the asphalt mixture didn